The implementation of the sustainable development goals at the national level:the case of the SDG Alliance Portugal - Leal, Susana (2019)
The 2030 Agenda for Sustainable Development set 17 Sustainable Development Goals (SDG) that should be nationally implemented. This implementation is based on the effective translation of sustainable development policies into concrete actions at the national level (and regional frameworks) (United Nations 2015). Portugal’s multilevel and multidimensional sustainability challenges (forestry, clean and efficient energy, and climate action, among others) impose a new agenda and require the redefinition of strategies (and missions) that implicate the local, regional and national engagement in meeting the SDGs, namely by promoting local and regional intervention (always with high societal relevance and sustainability purposes) to cope with the targets established in ‘Transforming our world: the 2030 Agenda for Sustainable Development’ (United Nations 2015). In Portugal, the United Nations Global Compact Network Portugal (UN-GCNP), with the support of the United Nations Global Compact (UNGP), found the SDG Alliance Portugal (http://globalcompact.pt/alianca-ods), a national multi-stakeholder platform, whose mission is to raise awareness, inform, implement, monitor, and assess the contribution of the business sector to SDG at the national level. It is as important to define goals and targets, as it is to create performance indicators to help in controlling and evaluating the SDGs (United Nations 2015). The research question that supports this chapter is: “How is the SDG Alliance Portugal engaging and increasing the contributions of the business sector and other civil society partners to turn into practice the SDGs actively?” Following this, the aims of the study are: (1) to describe the objectives, strategy, and practical initiatives of the SDG Alliance Portugal to contribute to the 2030 Agenda for Sustainable Development, (2) to describe the collaborative network and multi-stakeholder approach implemented to achieve the SDGs and targets. This research question and these goals will be addressed following the method of a single-case study (Yin 2003).